EFEKTIVITAS BIMBINGAN KLASIKAL METODE PROBLEM BASED LEARNING TERHADAP KONTROL DIRI SISWA SMP N 34 SEMARANG - ghfiroh, Ima; Fitriana, Siti; Widiharto, Chr.Argo (Jurnal Psikoedukasia, 2023)
The purpose of this research is to find out how effective the classical guidance service is the problem based learning method to increase students' self-control. This research method uses a true experimental design with a pretest-posttest control group design research technique. The population in this study was class XI A-IX G, with a total of 233 students. The sample in this study was IX A as the experimental group and IX G as the control group. The sampling used is cluster sampling random sampling. The results of the analysis of this study were known to test the hypothesis obtained by post-test data with a sig value of 0.000 <0.05, which means there is a difference in the increase in students' self-control towards the group given the classical guidance treatment using the problem-based learning method. Based on the results of this study, suggestions that can be conveyed are that classical guidance services with the problem based learning method can be used by counseling teachers to improve students' self-control.